2013
DOI: 10.1002/mds.25613
|View full text |Cite
|
Sign up to set email alerts
|

Framework for understanding balance dysfunction in Parkinson's disease

Abstract: People with Parkinson’s disease (PD) suffer from progressive impairment in their mobility. Locomotor and balance dysfunction that impairs mobility in PD is an important cause of physical and psychosocial disability. The recognition and evaluation of balance dysfunction by the clinician is an essential component of managing PD. In this review, we describe a framework for understanding balance dysfunction in PD to help clinicians recognize patients that are at risk for falling and impaired mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
170
0
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(206 citation statements)
references
References 93 publications
(127 reference statements)
10
170
0
26
Order By: Relevance
“…This suggests that postural responses are complex phenomena. Although ability to take large steps and step quickly are significant contributors, deficits in proprioceptive integration and response scaling (23), impaired sense of vertical (5,24), asymmetry in balance control (6), or impairments in executive function (5,25) probably also contribute to postural impairments. The correlational results were comparable for the full sample and for the sub-groups of freezers and non-freezers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that postural responses are complex phenomena. Although ability to take large steps and step quickly are significant contributors, deficits in proprioceptive integration and response scaling (23), impaired sense of vertical (5,24), asymmetry in balance control (6), or impairments in executive function (5,25) probably also contribute to postural impairments. The correlational results were comparable for the full sample and for the sub-groups of freezers and non-freezers.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports of whether postural responses can be directly altered with training (5,7,23,(30)(31)(32); conversely there is strong evidence to support improvements in gait parameters with a variety of interventions (for review, see (33)). One study found that 2 weeks of training with repeated perturbations not only increased compensatory step length and reduced delay in compensatory step initiation, but also increased stride length and velocity in voluntary gait (31), demonstrating the potential for generalized improvements across both gait and postural responses with targeted training for only 1 of these components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Our cohort consisted primarily of subjects in Hoehn & Yahr stages 1-3 (99.2%) who did not manifest significant festination at the time of study. Unlike festination, slowing of gait speed can be seen even in de novo and early PD, 5,6 which likely reflects early impairments of multisystem neuronal compensatory mechanisms, 7 and appears to signal the presence of cortical cholinergic terminal loss superimposed upon nigrostriatal dopaminergic denervation. 1 Progressive stooping and postural impairments, seen commonly in more severe stages of PD, are likely significant contributors to festinating gait.…”
Section: Higher Glucose Levels Associated With Lower Memory and Reducmentioning
confidence: 99%
“…Pharmacological research suggests that poor balance in this population is due to malfunctioning afferent sensory integration and decreased 5,6 efferent neuromuscular signals in the central nervous system (CNS). However there is also evidence that balance can worsen with these pharmacological interventions, suggesting 2,7 there are other contributors to fall risk in this population.…”
Section: Introductionmentioning
confidence: 99%